TỔNG HỢP KETIMIN LÀM CHẤT ĐÓNG RẮN CHO MÀNG PHỦ NHỰA EPOXY TỪ DIETYLENTRIAMIN (DETA) VÀ METYLIZOBUTYLXETON (MIBK) - Bích Thuỷ, Nguyễn Thị; Anh, Nguyễn Đức (Vietnam Journal of Chemistry, 2012)
Ketimine is one of the epoxy room temperature curing agents which can cure epoxy resins in high humidity. It simultaneously can overcome the disadvantages of traditional curing agents as aliphatic amines. In this article, ketimine based on diethylenetriamine and methylisobutylketone was synthesized. The obtained ketimine has been characterized by IR spectroscopy, specific gravity, refraction index, total nitrogen content, amino index and molecular refraction. Some parameters which affect to the performance of ketimine synthesis processing as the absence of analysis, the content of analysis, solvents, reaction time, etc… are measured. The conditions to synthesis ketimine have been defined. It has been found that the performance of processing is high and stable.